South-South Dialogue: In Search of Humanity - Mukandi, Bryan (The Australian Journal of Indigenous Education, 2017)
This paper is a meditation on the idea of South-South dialogue, beginning with the South-South Dialogues: Situated Perspectives in Decolonial Epistemologies symposium held at the University of Queensland in 2015. I interrogate the concept of South-South dialogue, apposing it to the Cartesian ‘I think’, and then question the plausibility of the concept. On the basis of a Gadamerian conception of understanding, I suggest that what passes for South-South dialogue is in fact more likely to be North-South or even North-North dialogue. This is buttressed by an examination of Valentin Mudimbe's Parables and Fables. I go on to suggest, however, that by staying within the realm of the concept, in what could be called a Cartesian paradigm, Mudimbe misses the important role that South-South dialogue can play. Drawing on the work of Sara Motta, Tsitsi Dangarembga's Nervous Conditions and the concept of hunhu, I claim that the promise of South-South dialogue is the creation of spaces in which humanity is fostered.